STRUCTURAL GUIDANCE STUDY FOR LARGE POLAR ICEBREAKER. LARGE POLAR ICEBREAKER FOR UNITED STATES COASTGUARD. - LLOYD'S REGISTER OF SHIPPING LONDON (ENGLAND) RESEARCH AND TECHNICAL ADVISORY SERVICES DEPT (1967)
The object of these analyses is to determine the structural effectiveness of two large polar icebreakers designed from two different structural philosophies and to compare the advantages and disadvantages of one structural system with another. Two computer programs have been utilized for the analyses, a three dimensional elastic analysis and a two dimensional elastic analysis. (Author) See also AD-679 972.